Implementation of a Mobile Web-Based Information Sharing Forum Information System - Muhammad Muslihudin; Miftahuddin Miftahuddin; Kanti Lestari (Tech-E, 2020)
The mobile web-based knowledge sharing forum information system is one of the media that utilizes the internet as a means of gathering and discussing to exchange information for people who want to share their knowledge with people who have not yet studied. With this forum, the public can find out which regions are still taking a lot of education and can make organizations so that they can share their knowledge with the community. The process of creating a mobile web-based knowledge sharing forum information system by analyzing an existing system using the SDLC method. Mobile web-based knowledge sharing forum information system is one of the media that utilizes the internet as a means of gathering and discussing to exchange information for internet users who want to share their knowledge with people who have not yet studied